Karakteristik Organoleptik Daging Domba yang Diberi Stimulasi Listrik Voltase Rendah dan Injeksi Kalsium Klorida - T Suryati; M Astawan; T Wresdiyati (Faculty of Animal Science, Bogor Agricultural University, 2006)
Effect of low voltage electrical stimulation (LVES; 45 volt, 3 amps for approx 100 sec) and CaCl2 injection on sensory characteristic of mutton were evaluated. Six mutton were divided into 3 groups slaughtered. One carcass of each group was subjected to LVES treatment within 30 min postmortem (PM). After LVES, longissimi thoracis et lumborum muscles were removed and treated: without CaCl2 injection, CaCl2 injection (200 mM, 5% w/w) 2 h and 24 h PM. Samples were stored in a vacuum pack at 1 ± 10C. Results showed that LVES could be used to improve colour of meat. CaCl2 injection, especially without LVES produced smooth mutton texture. CaCl2 injection 24 hr PM without LVES decreased meat elasticity. LVES with CaCl2 injection 2 hr PM was the best treatment to produce fresh mutton with good sensory characteristic. Key words : mutton, electrical stimulation, CaCl2, sensory characteristic